Obesity‐initiated metabolic syndrome promotes urinary voiding dysfunction in a mouse model. Issue 11 (4th April 2016) - He, Qiqi; Babcook, Melissa A.; Shukla, Sanjeev; Shankar, Eswar; Wang, Zhiping; Liu, Guiming; Erokwu, Bernadette O.; Flask, Chris A.; Lu, Lan; Daneshgari, Firouz; MacLennan, Gregory T.; Gupta, Sanjay
Abstract : OBJECTIVE: Accumulating evidences suggests that obesity and metabolic syndrome (MetS) contribute towards lower urinary tract symptoms (LUTS) through alterations in the phenotype of bladder and prostate gland. Clinical studies indicate a link between MetS and LUTS. Nevertheless, there is lack of suitable animal model(s) which could illustrate an association linking obesity to LUTS. We examined the lower urinary tract function in an obesity‐initiated MetS mouse model. METHODS: Male C57BL/6N wild‐type and obese B6.V‐Lepob/J maintained on regular diet for 28 weeks were subjected to the assessment of body weight (BW), body length (BL), waist circumference (WC), body mass index (BMI), blood glucose (BG), plasma insulin (INS), plasma leptin (LEP), total cholesterol (CHO), free fatty acid (FFA), and measurement of urinary functions. Whole animal peritoneal and subcutaneous adipose tissue measurements as well as prostate and bladder volumes were analyzed by MRI followed by histological evaluation. These parameters were used to draw correlations between MetS and LUTS. RESULTS: Obesity parameters such as BW, WC, and BMI were significantly higher in B6.V‐Lepob/J mice compared to C57BL/6N mice ( P < 0.01). Higher levels of total CHO and FFA were noted in B6.V‐Lepob/J mice than C57BL/6N mice ( P < 0.05). These results were concurrent with frequency, lower average urine volume and other urinary voiding dysfunctions in B6.V‐Lepob/J mice. MRI assessments demonstrate marked increase in body fat and prostate volume in these mice. Compared to C57BL/6N mice, histological analysis of the prostate from B6.V‐Lepob/J mice showed increased proliferation, gland crowding, and infiltration of immune cells in the stroma; whereas the bladder urothelium was slightly thicker and appears more proliferative in these mice. The regression and correlation analysis indicate that peritoneal fat (R = 0.853; P < 0.02), CHO (R = 0.729; P < 0.001), BG (R = 0.712; P < 0.001) and prostate volume (R = 0.706; P < 0.023) strongly correlate with LUTS whereas BMI, WC, INS, and FFA moderately correlate with the prevalence of bladder dysfunction. CONCLUSION: Our results suggest that LUTS may be attributable in part to obesity and MetS. Validation of an in vivo model may lead to understand the underlying pathophysiological mechanisms of obesity‐related LUTS in humans. Prostate 76:964–976, 2016 . © 2016 Wiley Periodicals, Inc.